Pengetahuan Remaja Anak Jalanan Tentang Bahaya Seks Bebas dan Penyakit Menular Seksual di Komunitas Peduli Anak Kelurahan Medan Maimun - Nur Asiah; Nur Asnah Sitohang; Dewi Elizadiani Suza (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
Reproductive health and adolescent understanding of the dangers of free sex and sexually transmitted diseases in Indonesia is still low, this can be seen from the many cases of pregnancy outside of marriage, dating violence and abortion with high-risk drugs. Adolescent's understanding of reproductive health is a provision for adolescents to behave in a healthy and responsible manner. Not all adolescents have received sufficient and correct information about reproductive health. Street children are a group of children who are on the side of the road or on the road, who carry out activities in the hope of earning money for life. Knowledge and attitudes towards personal hygiene of reproductive organs are also poor in terms of research results. Therefore they need to be given counseling, guidance and support, so that healthy growth and development can occur so that one day these teenagers will become healthy adults physically, spiritually and socially through the formation of health cadres. This community service is carried out on street teenagers in the Community Caring for Children (KOPA) Medan Maimun. Medan city. The methods used in this activity are: 1. Health education with material on adolescent reproductive health, the dangers of free sex behavior and sexually transmitted diseases; 2. Cadre training; 3. Assistance of cadres in conducting counseling to peers (peer group). 4. Evaluation of the success of the program: post-test for outreach cadres and youth participants. The data analysis used was univariate. The number of respondents 25 people. The results showed that the majority of the Padang ethnic group (76%), junior high school education (54%), father and mother still (father 80% and mother 92%), education of 80% high school parents. The results of the questionnaire on knowledge were still there (44%) street children had not answered questions about the symptoms of HIV/AIDS. Symptoms of HIV/AIDS include fever, night sweats, continuous diarrhea, fatigue, and persistent coughing and weight loss. They also have not all answered correctly on the question of gangrene is a type of sexually transmitted infection (24%), mode of transmission of sexually transmitted diseases (20%); and HIV/AIDS can cause death (20%). This is because young children have never received this information either at school or from their parents. Researchers suggest that the KOPA manager should actively cooperate with the nearest PUSKESMAS to provide information about the dangers of free sex and sexually transmitted diseases.